PENGARUH MANAJEMEN LABA, KINERJA KEUANGAN, DAN UKURAN KAP TERHADAP OPINI AUDIT GOING CONCERN - Rosyati, Tati; Fitriyana, Fina (Journal of Research and Publication Innovation, 2023)
This research aims to determine and provide empirical evidence of the influence of earnings management, financial performance and KAP size on going concern audit opinions in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021. This research method uses quantitative methods using observations in the form of panel data processed using eviews10. Logistic Regression Analysis. The sample selection in this study used a purposive sampling technique, which obtained 15 companies. The results of this study partially show that earnings management, financial performance as proxied by (Market Ratio, Activity Ratio), and KAP Size have no influence on Going Concern Audit Opinion. Simultaneously, Profit Management, Activity Ratios, Market Ratios and KAP Size jointly influence going concern audits.